Mechanical properties of sintered aluminum alloy compacts - Hrairi, Meftah; Mohamad Ravi, Fadzly (IIUM Press, 2011)
Aluminum alloy A356 is used in automotive transmission cases, water cooled cylinder blocks, pistons, connecting rods, and also other moderate strength components [1]. Pistons are made from materials having properties such as high compressive strength and high hardness in order to handle the high temperature and pressure produced in the cylinder while combustion strokes take place. Pistons also need to have high corrosive resistance because they are exposed to highly combustible air and fuel mixtures. The reciprocating piston that goes up and down in motion also needs to be very wear resistant in order to maintain a longer life cycle of the piston. Based on the experimental study conducted in this work, the A356 produced parts using the P/M process seem to have better mechanical properties than similar parts produced using the conventional permanent mold cast process. This A356 material can also be applied to make the engine valves which require very similar characteristics to the piston